In Praise of Under-Specification? - Cerf, Vinton G. (Communications of the ACM, 2017)
The author considers the benefits of under-specification. He uses the examples of Internet Protocol (IP) specifications that lack information about routing and how under-specification in manufacturing can allow for technological innovation and money savings. Other topics include Boolean representation, IP packet payloads, and security and interoperability.